Pengaruh Karakteristik Perusahaan Terhadap Kualitas Pelaporan Keuangan dan Dampaknya Terhadap Efisiensi Investasi - Teguh Budi Raharjo (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
This study analyzes and describes the condition of the financial reporting quality manufacturing company in Indonesia, determinants and impact. The deciding factor analyzed the quality of financial reporting is characteristic of companies that include the structure of the company (firm structure), monitoring the company (firm monitoring) and firm performance. While the method of nanalysis performed by Path Analysis. The study concluded that of the three variables that were analyzed, only performance and monitoring variables proved to affect the quality of financial reporting. The variable structure of the companies does not affect the quality of financial reporting. Associated with the efficiency of investment, generally of four independent variables were analyzed (structure, monitoring, performance, quality financial reporting) affect not directly on the efficiency of investment.